Characterization of Fusarium Wilt Resistance in Diverse Chickpea (Cicer arietinum L.) Genotypes using Established Molecular Markers - Babu, D. Ratna; Ravikumar, R. L. (International Journal of Bio-resource and Stress Management, 2023)
Chickpea cultivation is much affected due to wilt caused by Fusarium oxysporum f. sp. ciceris race 1. Two major loci H1 and H2 determine the disease reaction to race 1 of this pathogen in chickpea. Dominant alleles at both loci (H1_H2_) result in early wilting reaction, homozygous recessive at either of the loci (H1_h2h2 or h1h1H2_) results in late wilting reaction while homozygous recessive at both loci (h1h1h2h2) leads to resistance. An Allele Specific Associated Primer (ASAP), CS-27700 and an RAPD marker, A07C417 are linked to susceptibility at H1 and H2 loci, respectively. In the present study sixteen diverse genotypes from different genetic backgrounds were screened using the above two established molecular markers. The ASAP marker CS-27700 linked to H1 locus was present in five genotypes viz., ICC-12236, Karikadli, ICC-12434, JG-62 and ICC-12429. The RAPD marker A07C417, linked to H2 locus, was present in all genotypes except in ICC-12249, WR 315 and ICC-12236. The absence of both the markers, CS-27700 and A07C417 (h1h1h2h2) indicated the resistant reaction in the genotypes ICC-12249 and WR-315. While presence of both the markers (H1H1H2H2) in Karikadli, ICC-12434, JG-62 and ICC-12429 indicated the early wilting reaction and presence of either of the markers (H1_h2h2 or h1h1H2_) in other genotypes (A-1, ICCV-2, ICC-96030, ICC-4958, ICC-96029, BG-256, K-850, ICC-12237, ICC-12252, ICC-12236) indicated late wilting reaction. Thus, these established molecular markers at DNA level facilitated easy and early identification of susceptible or resistant lines. Utilization of these markers in plant breeding will be complementary to the conventional breeding which can hasten up its progress.